Penerapan Konseling Rasional Emotive Behaviour untuk Mengubah Konsep Diri Wanita Lesbian - Triadhari, Imelda; Masriah, Masriah; Salsabila, Hana Haifa; Aminaturrahma, Aminaturrahma (IAIN Syekh Nurjati Cirebon, 2024)
Rational Emotive Behavior Therapy (REBT) is an approach that requires humans to think and feel, although behavior is limited between the two, namely thoughts and feelings that influence at the same time. The counselee's problems are caused by a number of triggers, including the role of the mother who dominates home activities more than the father who has a tendency to be indifferent and rude to the counselee, associations that normalize sexual deviations and the counselee's partner who always hurts him. Since then the counselee stopped trusting the opposite sex and started trusting and liking the same sex. Finally, the condition of the counselee who experiences problems within himself is then supported by environmental conditions and situations that are not good, causing the counselee to fall into and follow these deviations. The purpose of using this case study research is to see an event or phenomenon in a person and do it in depth to find out the background of the event that happened to that person. Another goal is to make the counselee understand that his behavior in liking the same sex (lesbian) is something that deviates from the norms and rules that apply. Rational Emotive Behavior Therapy (REBT) is an approach that requires humans to think and feel, although behavior is limited between the two, namely thoughts and feelings that influence at the same time. The counselee's problems are caused by a number of triggers, including the role of the mother who dominates home activities more than the father who has a tendency to be indifferent and rude to the counselee, associations that normalize sexual deviations and the counselee's partner who always hurts him. Since then the counselee stopped trusting the opposite sex and started trusting and liking the same sex. Finally, the condition of the counselee who experiences problems within himself is then supported by environmental conditions and situations that are not good, causing the counselee to fall into and follow these deviations. The purpose of using this case study research is to see an event or phenomenon in a person and do it in depth to find out the background of the event that happened to that person. Another goal is to make the counselee understand that his behavior in liking the same sex (lesbian) is something that deviates from the norms and rules that apply.Keywords: REBT, Lesbian, Counseling